2022
DOI: 10.1186/s12885-022-09848-y
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic propofol enhances cisplatin-sensitivity of non-small cell lung cancer cells through N6-methyladenosine-dependently regulating the miR-486-5p/RAP1-NF-κB axis

Abstract: Background Drug resistance is a considerable challenge for chemotherapy in non-small cell lung cancer (NSCLC). Propofol, a commonly used intravenous anesthetics, has been reported to suppress the malignancy of various cancers. However, the effects of propofol on cisplatin (DDP) sensitivity in NSCLC and its molecular mechanisms have not been clearly clarified yet, and the present study aimed to resolve this problem. Methods NSCLC cells were co-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Moreover, the overexpression of miR-486-5p attenuated tumor growth and inhibited metastasis according to in vivo assays [36,37]. A recent study showed that the anesthetic propofol induced the expression of miR-486-5p, resulting in the inhibition of the Ras-associated protein1-NF-κB pathway [38]. These events contributed to cisplatinsensitivity in NSCLC cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overexpression of miR-486-5p attenuated tumor growth and inhibited metastasis according to in vivo assays [36,37]. A recent study showed that the anesthetic propofol induced the expression of miR-486-5p, resulting in the inhibition of the Ras-associated protein1-NF-κB pathway [38]. These events contributed to cisplatinsensitivity in NSCLC cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Represented by the most learned METTL3, it was revealed that METTL3 promoted resistance to cisplatin by stimulating AKT1 in NSCLC [ 35 ]. However, Ling et al found that METTL3 participated in the re-sensitization to cisplatin mediated by propofol [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Ling et al found that propofol enhanced cisplatin sensitivity dose-dependently via promoting METTL3-mediated m6A methylation. Propofol augments m6A enrichment on pri-miR-486-5p to promote its maturation and further inactivates the Ras-associated protein1 (RAP1)-NF-kappaB (NF-κB) axis, and knockdown of METTL3 reversed the promoting effect [ 36 ]. Besides, METTL3 was negatively regulated by miR-4443, which is enriched in exosomes of cisplatin-resistant NSCLC.…”
Section: Platinum Drugsmentioning
confidence: 99%
“…Recent studies have shown that propofol, an intravenous anesthetic agent traditionally and widely used for sedation and general anesthesia, exhibits anti-tumor activity against cancer progression in vitro and in vivo (Wang et al, 2018;Gu et al, 2022). Propofol can boost the anti-tumor activity of cisplatin in lung cancer (Huang et al, 2020;Ling et al, 2022;Quan et al, 2022). Mechanistically, propofol decreases cisplatin resistance in NSCLC by inducing ferroptosis, accomplished by upregulating the miR-744-5p/miR-615-3p axis and inhibiting GPX4 .…”
Section: Reversing Chemotherapy Resistance Through Inducing Ferroptos...mentioning
confidence: 99%